Health Status and Health Behaviors of People Living in a Condominium of Urban Area, Thailand - บุญนาค ศุภรัตน์; พูลสวัสดิ์ นิติรัตน์; จันทร์เพ็ง สุทธิสา; สรรพอาษา เวสารัช (Journal of Health Science of Thailand, 2023)
The aims of study were to determine the health status and health behaviors of residents aged 18 years and over in a condominium of urban area in the year 2017. It was conducted as a survey research. Simple random sampling was applied to select with drawing room numbers from all rooms on the list of 1,479 condominium units enrolled subjects. Data for the study collected through a questionnaire. The study results showed that most of respondents were female (58.6%). The majority average aged 34 years old. Most of them own a room, 56.7%, followed by renting (27.8%). Majority of them knew other residents of the same condominium (50.3%). For the health status and behaviors data, it was found that body mass index (BMI) was normal in 35.6% of male and 46.9% of female respondents. Most of them had low stress level (55.0%). The percentage of health behaviors data in male who drank alcohol, smoking, and exercise were 70.3%, 14.4%, 17.4%, respectively; and those for females who drank alcohol, smoking, and exercise were 51.8%, 4.3%, 29.3%, respectively. Therefore, health promotion program and healthcare services should be provided to prevent illnesses among condominium residents in the urban areas. Moreover, programs for risk communication and public relation on health knowledge and disease prevention including mental health care should be initiated, including the establishment of health clubs.